المسؤولية الجنائية في ضوء معايير القدرة السلوكية والنفسية - أ.د. كمال الأمين محمد فضل الله; د. نجوى عبد الرازق عباس طه (White Nile Journal for Studies and Research, 2023)
The study dealt with the standards of behavior and their impact on criminal responsibility, with the aim of defining behavior and mental illness and explaining its reality, clarifying the standards of normal behavior, and studying the historical development of criminal responsibility for the mentally ill. On the objectives of the study and the problematic that it addresses, the study followed the descriptive analytical approach and the explanatory case study. One of the results of the study is the need to distinguish between the legal and medical concepts of mental illness, because the legal concept is concerned with revealing the degree of influence in the mental properties that make up the person’s ability to perceive and choose. The lesson is in the field of denying criminal responsibility Or reduce it through the impact of the defect in normal behavior, and among the recommendations of the study is to promote the dissemination of criminal psychology, and the development and modernization of the reformulation of existing laws and legislation to keep pace with medical and societal developments.